Knock-out of nexilin in mice leads to dilated cardiomyopathy and endomyocardial fibroelastosis - Aherrahrou, Zouhair; Schlossarek, Saskia; Stoelting, Stephanie; Klinger, Matthias; Geertz, Birgit; Weinberger, Florian; Kessler, Thorsten; Aherrahrou, Redouane; Moreth, Kristin; Bekeredjian, Raffi; Hrabě de Angelis, Martin; Just, Steffen; et al. (Basic research in cardiology, 2016)
Cardiomyopathy is one of the most common causes of chronic heart failure worldwide. Mutations in the gene encoding nexilin (NEXN) occur in patients with both hypertrophic and dilated cardiomyopathy (DCM); however, little is known about the pathophysiological mechanisms and relevance of NEXN to these disorders. Here, we evaluated the functional role of NEXN using a constitutive Nexn knock-out (KO) mouse model. Heterozygous (Het) mice were inter-crossed to produce wild-type (WT), Het, and homozygous KO mice. At birth, 32, 46, and 22 % of the mice were WT, Het, and KO, respectively, which is close to the expected Mendelian ratio. After postnatal day 6, the survival of the Nexn KO mice decreased dramatically and all of the animals died by day 8. Phenotypic characterizations of the WT and KO mice were performed at postnatal days 1, 2, 4, and 6. At birth, the relative heart weights of the WT and KO mice were similar; however, at day 4, the relative heart weight of the KO group was 2.3-fold higher than of the WT group. In addition, the KO mice developed rapidly progressive cardiomyopathy with left ventricular dilation and wall thinning and decreased cardiac function. At day 6, the KO mice developed a fulminant DCM phenotype characterized by dilated ventricular chambers and systolic dysfunction. At this stage, collagen deposits and some elastin deposits were observed within the left ventricle cavity, which resembles the features of endomyocardial fibroelastosis (EFE). Overall, these results further emphasize the role of NEXN in DCM and suggest a novel role in EFE.
Published online: 10 December 2015
Gesehen am 12.08.2020